Strategi Kreatif Tim Produksi Life Channel dalam Program Way Out di MNC Channels - Sally Christine Idealna Nainggolan; Elpa Hermawan; Ondy Ondy (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In the era of globalization and increasingly advanced technology such as television, there are many television stations that try to compete to present inspiring, educational, and entertaining programs. Way Out is a Christian religious program that is present on MNC Channels TV station on Life Channel. This study aims to determine the creative strategy used by the Life Channel production team in designing and presenting the Way Out program. In this study, the researcher used a qualitative method with a descriptive approach and the theory used was Wallas communication theory. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study found that the creative strategy of the production team was the key to the success of the Way Out program on Life Channel as a religious show that was relevant to its audience. Through a creative approach that is realized through strong visual narratives, a relaxed communication style, and a planned production process. With teamwork and the use of social media, it also expands the reach and involvement of the audience. This program proves that spiritual content can be packaged in a modern, inspiring, and impactful way in the digital era.